Optimization design based approach for the determination and minimization of the displacement under tensile load in hybrid composite joint - Fouzia Merabbi; Abdelkader Lousdad; Abdelkader Megueni; Abderahmane Sahli (Fracture and Structural Integrity)
Composite materials are most often used for lengthier and thin structures susceptible to buckle. The optimization is often carried out taking into consideration the resistance to buckling and tensile loads for minimum displacement i.e maximization of the tensile load for composite assembly joint. It well known that nowadays that composite material in structural mechanics is widely used in many industrial sectors such as in aerospace and aeronautic, automobile, marine industries as well as in and civil engineering. Composite materials are attractive due to their advantages and performance i.e: lighter weights, high resistance to thermal and mechanical loads, resistance to corrosion and wear. In this paper an investigation is focused on the problem of hybrid assembly joint (bolted bonded) composite structures. The aim is the optimization of the main influencing parameters.